Analisis Nilai Pendidikan Karakter Novel “Orang-orang Biasa” Karya Andrea Hirata terhadap Relevansi Pembelajaran Cerpen - Dina Siti Patimah Dewi; Diena San Fauziyah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The purpose of this study is to 1) find out the values of character education in the novel "ordinary people" by Andrea Hirata 2) find out the relevance of the character education value of the novel "ordinary people" in the learning of short stories. The research method used is qualitative descriptive. Data collection in this study uses a literature technique with content analysis. Some of the steps to collect data in the novel Ordinary People, 1) The researcher reads the novel as a whole carefully, 2) Records or marks words and sentences related to the formulation of the problem, such as the structure of the novel, as well as sentences that show the values of character education, and 3) Identifies the values of character education contained in this novel. The results of this research found 5 values of character educators, namely honesty, discipline, hard work, independence, and democracy. From the results of the above analysis, 10 analysis data were found. The results of this study can be relevant to the learning of short story texts contained in KD 3.5 Identifying the elements that build literary works in short story texts that are read or heard and can affect the formation of student character in accordance with the strengthening of the Pancasila student profile that applies to the Independent curriculum.